Unusual Presentation of Pulmonary Tuberculosis with Massive Haemothorax Leading to Obstructive Shock: A Case Report - Yudith Megumi Rebhung; Swempi Melchiadi Abolla; Januario E Bria; Charles Saputra (Riviera Publishing, 2026)
Introduction : Tuberculosis (TB) remains a major global health burden and continues to pose significant diagnostic challenges due to its nonspecific clinical manifestations. Although pleural effusion is a common extrapulmonary manifestation of TB, massive spontaneous haemothorax leading to obstructive shock is exceedingly rare and potentially life-threatening. Case Description : We report the case of a 56-year-old male who presented with progressive dyspnea and was initially diagnosed with cardiogenic shock and acute decompensated heart failure at a referring hospital. Physical examination revealed hypotension, tachycardia, tachypnea, elevated jugular venous pressure, and decreased breath sounds over the left lung. Imaging demonstrated massive left-sided pleural effusion with mediastinal shift. Bedside transthoracic echocardiography showed preserved biventricular function with significant extrinsic cardiac compression. Emergency chest tube placement evacuated approximately two liters of blood, resulting in rapid hemodynamic improvement, confirming the diagnosis of obstructive shock secondary to massive spontaneous haemothorax. Despite negative molecular testing for tuberculosis from sputum and pleural fluid, chest computed tomography revealed findings highly suggestive of pulmonary tuberculosis. Anti-tuberculosis therapy was initiated, leading to further clinical improvement. The patient was discharged in stable condition after five days of hospitalization. Conclussion : This case underscores pulmonary tuberculosis as a rare etiology of massive spontaneous haemothorax causing obstructive shock. Early recognition of obstructive shock, prompt mechanical decompression, and thorough etiological evaluation are critical for optimal outcomes. In the absence of microbiological confirmation, radiological findings play a pivotal role in establishing a diagnosis of clinically confirmed tuberculosis, and early initiation of anti-tuberculosis therapy may be lifesaving